2012
DOI: 10.1002/xrs.2438
|View full text |Cite
|
Sign up to set email alerts
|

XAFS analysis of indium oxynitride thin films grown on silicon substrates

Abstract: Local structure of indium oxynitride thin films grown on silicon substrates was investigated by X-ray absorption fine structure technique incorporated with first principle calculations. The thin films were grown by using reactive gas timing radio frequency (RF) magnetron sputtering technique with nitrogen (N 2 ) and oxygen (O 2 ) as reactive gasses. The reactive gasses were interchangeably fed into sputtering system at five different time intervals. The gas feeding time intervals of N 2 :O 2 are 30 : 0, 30 : 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The authors in ref found the band gap of 1.8–2.0 eV for InN and claimed that the reason for an increased band gap is the formation of optically transparent solid solution of InN–In 2 O 3 at an oxygen concentration of about 20%. Several other authors also suggested a solid solution between InN and In 2 O 3 and found an increased band gap. Note that, the positions of all Gaussians remain at the same position for different excitation energies.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The authors in ref found the band gap of 1.8–2.0 eV for InN and claimed that the reason for an increased band gap is the formation of optically transparent solid solution of InN–In 2 O 3 at an oxygen concentration of about 20%. Several other authors also suggested a solid solution between InN and In 2 O 3 and found an increased band gap. Note that, the positions of all Gaussians remain at the same position for different excitation energies.…”
Section: Resultsmentioning
confidence: 91%
“…More recently, it has been suggested that the larger band gap of InN upon incorporation of oxygen may be due to the formation of indium oxide nitride. Several authors , have studied indium oxide nitride at different oxygen concentrations and found that for higher oxygen concentrations, the thin film can be considered a solid solution between InN and In 2 O 3 , resulting in an increased band gap due to the large band gap (3.1 eV) of In 2 O 3 . Still, there is not any clear experimental and theoretical evidence addressing the effects of oxygen on the band gap but oxygen incorporation is commonly accepted and, thus, warrants investigation using element sensitive experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the relatively weak Zn–N bonds readily convert to Zn–O bonds; therefore, capping layers must be formed by thermal annealing or plasma treatment to prevent the evaporation of nitrogen. The present work consists of a study on a similar type of material, indium oxynitride (InON), which is often used for optoelectronic applications and also exhibits higher stability with respect to air exposure. TFTs incorporating this semiconductor exhibit reasonable switching characteristics and reliability under bias stress, and first principles calculations indicate that In–N bonds are stronger than Zn–N bonds, thus accounting for the higher durability when exposed to air.…”
Section: Introductionmentioning
confidence: 99%